Synthesis of deepoxy-4,5-didehydromethylenomycin a and methylenomycin a methyl esters - C. Mahidol (2018)
[±]-Deepoxy-4,5-didehydromethylenomycin A methyl ester 8 and [±] -methylenomycin A methyl ester 9 are synthesized from anthracene adduct 2 via a common intermediate 13. Flash vacuum pyrolysis of adduct 13 gives 8, while stereospecific epoxidation of 13 followed by pyrolysis yields 9. © 1989.